2019
DOI: 10.1002/ece3.5211
|View full text |Cite
|
Sign up to set email alerts
|

Convergent evolution of body color between sympatric freshwater fishes via different visual sensory evolution

Abstract: Although there are many examples of color evolution potentially driven by sensory drive, only few studies have examined whether distinct species inhabiting the same environments evolve similar body colors via shared sensory mechanisms. In this study, we tested whether two sympatric freshwater fish taxa, halfbeaks of the genus Nomorhamphus and ricefishes of the genus Oryzias in Sulawesi Island, converge in both body color and visual sensitivity. After reconstructing the phylogeny separately for Nomorhamphus and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 44 publications
0
7
0
2
Order By: Relevance
“…Furthermore, the retention of RH2C is an adaptation of turbot to the spectral environment in the deep sea due to its shortwave-shift of λ max . Additionally, some studies have shown that opsin genes are tied to nuptial and body coloration [ 36 , 37 ], but further work is required to confirm this function. Regarding the RH1 genes, all flatfish species studied herein have the substitution of D83N, which has been demonstrated to cause blue shift in cattle and chameleons [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the retention of RH2C is an adaptation of turbot to the spectral environment in the deep sea due to its shortwave-shift of λ max . Additionally, some studies have shown that opsin genes are tied to nuptial and body coloration [ 36 , 37 ], but further work is required to confirm this function. Regarding the RH1 genes, all flatfish species studied herein have the substitution of D83N, which has been demonstrated to cause blue shift in cattle and chameleons [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the retention of RH2C is an adaptation of turbot to the spectral environment in the deep sea due to its short-shift of λ max . Additionally, some studies have shown that opsin genes are tied to nuptial and body coloration [31,32], but further work is required to confirm this function. Regarding the RH1 genes, all flatfish species studied herein have the substitution of D83N, which has been demonstrated to cause blue shift in cattle and chameleons [33].…”
Section: Molecular Evolution Of Rh2 and Rh1mentioning
confidence: 99%
“…34-36 Finally, to identify genes that are associated with populations with different genetic heritability or environmental quality, transcriptome analysis using RNA-seq procedure can be performed. 37,38…”
Section: Some Selected Molecular Computational and Bioinformatics Tmentioning
confidence: 99%